HYDROGENATION OF PALM OIL ON Pt-CONTAINING CATALYSTS - Massenova Alma Tulegenovna; Sass Alexander Sergeevich; O.A.Frolova; Kenzin Nail Rashidovich; Kalykberdiyev Maksat Kuatovich; Baiken Amankeldi (Academic Scientific Journal of Chemistry, 2019)
The article is devoted to the study of the catalytic hydrogenation of palm oil to obtain a high yield of fat without double bonds and trans-isomers. The catalysts used were platinum supported on various carriers - alumina, ball aluminosilicate, synthetic HY zeolite and activated carbon, among which ball aluminosilicate was the most active. The effect of process temperature and hydrogen pressure on the content of double bonds and transisomers of fatty acids was studied. In the temperature range of 80–200°C and pressures of 0.3–1.5 MPa, the content of C = C bonds decreases from 54 g I2/100g, and the content of trans fats from 22 to 0%. On the Pt/aluminosilicate catalyst at 200°C and 1.5 MPa, double bonds and trans-isomers of fatty acids are completely absent in the reaction products. Using the BET, porometry and EM methods, a uniform formation of zero-valence metal particles on the catalyst surface was established, and nanoscale particles of Pt were determined.